Curcumin reduces enteric isoprostane 8-iso-PGF2α and prostaglandin GF2α in specific pathogen-free Leghorn chickens challenged with Eimeria maxima - Victor M. Petrone-Garcia (Nature Portfolio, 2021)
Abstract The purpose of this pilot study was to evaluate and determine the concentration of prostaglandin GF2α (PGF2α) and isoprostane 8‐iso‐PGF2α in plasma and intestine of specific pathogen-free (SPF) Leghorn chickens challenged with Eimeria maxima, with or without dietary supplementation of curcumin using solid‐phase microextraction and ultra‐performance liquid chromatography/tandem mass spectrometry. Eighty 1-day-old male SPF chickens were randomly allocated to one of four groups with four replicates (n = 5 chickens/replicate). Groups consisted of: (1) Control (no challenge), (2) Curcumin (no challenge), (3) Eimeria maxima (challenge), and (4) Eimeria maxima (challenge) + curcumin. At day 28 of age, all chickens in the challenge groups were orally gavaged with 40,000 sporulated E. maxima oocysts. No significant differences (P > 0.05) were observed in the groups regardless of the treatment or challenge with E. maxima. Enteric levels of both isoprostane 8‐iso‐PGF2α and PGF2α at 7 days and 9 days post-challenge were significantly increased (P < 0.01) compared to the non-challenge control chickens. Interestingly, the enteric levels of both isoprostane 8‐iso‐PGF2α and PGF2α at 7 days post-challenge were significantly reduced in chickens fed curcumin, compared to control chickens challenge with E. maxima. At 9 days post-challenge, only levels of isoprostane 8‐iso‐PGF2α in the enteric samples were significantly reduced in chickens challenged with E. maxima supplemented with curcumin, compared with E. maxima challenge chickens. No differences of isoprostane 8‐iso‐PGF2α or PGF2α were observed in plasma at both days of evaluation. Similarly, no significant differences were observed between the challenge control or chickens challenge with E. maxima and supplemented with curcumin at both times of evaluation. The results of this pilot study suggests that the antioxidant anti-inflammatory properties of curcumin reduced the oxidative damage and subsequent intestinal mucosal over-production of lipid oxidation products. Further studies to confirm and extend these results in broiler chickens are required.